2017
DOI: 10.1111/jocn.13906
|View full text |Cite
|
Sign up to set email alerts
|

Family involvement in timely detection of changes in health of nursing homes residents: A qualitative exploratory study

Abstract: Aims and objectivesTo explore family perspectives on their involvement in the timely detection of changes in their relatives' health in UK nursing homes.BackgroundIncreasingly, policy attention is being paid to the need to reduce hospitalisations for conditions that, if detected and treated in time, could be managed in the community. We know that family continue to be involved in the care of their family members once they have moved into a nursing home. Little is known, however, about family involvement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
1
46
0
1
Order By: Relevance
“…It is therefore essential to be extremely vigilant in emphasising this dimension of family nursing care. In Mrs. Morgan's situation, as in most similar situations, the intimate partner relationship is extremely important as it influences the PA’s quality of life, well‐being and health, and may even slightly decrease the rate of infection and hospitalisation (Gaugler, ; Powell et al, ; Roberts & Ishler, ; Zimmerman, Gruber‐Baldini, Hebel, Sloane, & Magaziner, ). Thus, Mrs. Morgan's scenario illustrates how Florence integrates the immediate family.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore essential to be extremely vigilant in emphasising this dimension of family nursing care. In Mrs. Morgan's situation, as in most similar situations, the intimate partner relationship is extremely important as it influences the PA’s quality of life, well‐being and health, and may even slightly decrease the rate of infection and hospitalisation (Gaugler, ; Powell et al, ; Roberts & Ishler, ; Zimmerman, Gruber‐Baldini, Hebel, Sloane, & Magaziner, ). Thus, Mrs. Morgan's scenario illustrates how Florence integrates the immediate family.…”
Section: Methodsmentioning
confidence: 99%
“…These reviews analyzed the transfer process in view of nursing staff and general practitioners [13, 14, 16]. Several studies indicated that family members may play an important role in the NH, for example in the timely detection of changes in NHR’s health status [17] or acting as decision maker for the resident in case of dementia [18]. However, until now there does not exist an overview summarizing the perspectives of family members.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this connection, difficulties faced to obtain cooperation from the nursing home directors and relatives of the older adults admitted is relevant, which have also been reported by other authors [ 41 ]. The above may be due to the fact that, in our culture, it is commonly believed that individuals send their older relatives to live in a nursing home because they do not want to take on their care anymore [ 42 , 43 ], which leads to their refusal to provide information, for fear of stigma.…”
Section: Discussionmentioning
confidence: 99%